Distinct solid and solution state self‐assembly pathways of RADA16‐I designer peptide. (25th June 2013) - Cormier, Ashley R.; Lopez‐Majada, Juan M.; Alamo, Rufina G.; Paravastu, Anant K.
<x xml:space="preserve">Abstract</x> Solid state NMR measurements on selectively 13C‐labeled RADA16‐I peptide (COCH3–RADARADARADARADA–NH2) were used to obtain new molecular level information on the conversion of α‐helices to β‐sheets through self‐assembly in the solid state with increasing temperature. Isotopic labeling at the A4 Cβ site enabled rapid detection of 13C NMR signals. Heating to 344–363 K with simultaneous NMR detection allowed production of samples with systematic variation of α‐helix and β‐strand content. These samples were then probed at room temperature for intermolecular 13C–13C nuclear dipolar couplings with the PITHIRDS‐CT NMR experiment. The structural transition was also characterized by Fourier transform infrared spectroscopy and wide angle X‐ray diffraction. Independence of PITHIRDS‐CT decay shapes on overall α‐helical and β‐strand content infers that β‐strands are not observed without association with β‐sheets, indicating that β‐sheets are formed at elevated temperatures on a timescale that is fast relative to the NMR experiment. PITHIRDS‐CT NMR data were compared with results of similar measurements on RADA16‐I nanofibers produced by self‐assembly in aqueous salt solution. We report that β‐sheets formed through self‐assembly in the solid state have a structure that differs from those formed through self‐assembly in the solution state. Specifically, solid state RADA16‐I self‐assembly produces in‐register parallel β‐sheets, whereas nanofibers are composed of stacked parallel β‐sheets with registry shifts between adjacent β‐strands in each β‐sheet. These results provide evidence for environment‐dependent self‐assembly mechanisms for RADA16‐I β‐sheets as well as new constraints on solid state self‐assembled structures, which must be avoided to maximize solution solubility and nanofiber yields. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd.